The Usefulness of Output Gaps for Policy Analysis - Koske, Isabell (OECD Economics Department Working Papers, 2008)
Measures of the gap between actual and potential activity are used frequently as indicators of the economic cycle and play a vital role in the conduct of monetary and fiscal policy. Given that output and unemployment gap estimates are often subject to considerable revision over time, this paper investigates the uncertainty surrounding projections and early outturn estimates of such gaps and evaluates their usefulness for policy making in real time. Current-year projections and initial outturn estimates of the gaps both appear to provide a reasonably good picture of the business cycle over the period studied, but one-year-ahead projections perform rather poorly. Projections made at cyclical turning points are subject to greater revision than those made at other times. Revisions to output gaps appear to stem primarily from revisions to actual rather than potential GDP. Empirical results show that output gaps remain a significant influence on inflation, but their influence is now weaker than in the past, and the usefulness of output gap estimates for real-time inflation projections is limited. Revisions to real-time output gaps also generate revisions to real-time estimates of the fiscal stance, although typically these are relatively moderate. Despite the uncertainty attached to gap estimates, they remain useful for policymakers, helping to situate current economic developments